(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
As countries and car makers focus on goals like "going green," combating climate change, and so on, the present worldwide trend toward electric vehicles is expanding. The design of electric vehicles is an important aspect of this. Electric cars are powered by electricity generated by a power source, most often batteries. These batteries require charging. A charging station must be supplied for this reason. The charging stations or points transform the energy they have access to from a variety of sources into DC electrical energy for the automobile. These devices had to be willing to handle human input, namely the amount of power to be used, in order for the user to pay for what they need. In this paper, an electric car is charged using a local bank capacity, a PV Powerwall is available. This simulation sets the foundation for solar-powered electric vehicle (EV) charger designs.